طرابلس الغرب خلال العهد العثماني الأول م1711-1551 - شلبي هشام; ربعي رمزي (My University, 2022)
Summary During that period, the Ottomans were the ray of hope for the people and notables of Tripoli. Tripoli's appeal to the Ottoman Empire provided an opportunity for the latter to expand its geographic and governmental reach. Therefore, the Sultan accepted aid in 1551 AD. The Ottoman fleet commanders were able to end the Christian presence in Tripoli, which had lasted for more than forty years. This marked the beginning of a new chapter in the history of Tripoli as an Ottoman province directly subject to the rule of Istanbul. -------------------------------- الملخص ان انطواء ليبيا تحت سلطة الإمبراطورية العثمانية كان فعلا لابد منه فرضته الظروف الدولية آن ذاك وهو راجع للغزوات المسيحية على طرابلس التي بدأها الإسبان وأنهاها فرسان مالطا والتي دفعت بأهالي طرابلس الغرب الى البحث عن مخلص لهم من كيد الصليبين الذين عاثوا فسادا واضطهادا، وفي تلك الفترة كان العثمانيين هم بصيص أمل أهالي وأعيان طرابلس الغرب،وكان إستنجاد طرابلس بالدولة العثمانية فرصة لهذه الأخيرة لتوسيع نطاقها الجغرافي والسلطوي لذلك قبل السلطان الإغاثة سنة 1551م، وتمكن قادة الأساطيل العثمانية من انهاء الوجود المسيحي في طرابلس الذي دام أكثرمن اربعين سنة وفتحت منها صفحة جديدة في تاريخ طرابلس الغرب كإيالة عثمانية تخضع مباشرة لحكم اسطنبول ------------------------------- Résumé Durant cette période, les Ottomans représentaient une lueur d’espoir pour la population et les notables de Tripoli en Occident. L’appel de Tripoli à l’Empire Ottoman fut pour ce dernier l’occasion d’élargir son champ d’action géographique et autoritaire. Par conséquent, le sultan accepta des secours en 1551 après JC et les chefs des flottes ottomanes purent mettre fin à la présence chrétienne en Tripoli, qui a duré plus de quarante ans et a ouvert une nouvelle page de l'histoire de l'ouest de Tripoli En tant qu'État ottoman, il était directement soumis à la domination d'Istanbul.
Keywords: ليبيا، الإمبراطورية العثمانية، الإسبان، فرسان مالطا، العثمانيين